Evaluation of all dose components in the LVR-15 reactor epithermal neutron beam using Fricke gel dosimeter layers - Bartesaghi, G; Burian, J; Gambarini, G; Marek, M; Negri, A; Viererbl, L (Applied radiation and isotopes, 2009)
Fricke gel dosimeters in the form of layers are suitable to reconstruct bidimensional distributions of the absorbed dose; in accordance with their chemical composition and applying suitably developed algorithms, they can provide dose images of the different radiation components in a BNCT field. After the description of the applied method, this work presents the results obtained at the epithermal column of the BNCT facility at the NRI in Rez (CZ). The measured dose distributions are shown in comparison with data taken by means of other dosimeters thermoluminescence dosimeters (TLDs) and with calculations carried out with the Monte Carlo code MCNP5. The agreement with the results obtained by means of the different techniques is satisfying.
Keywords: Animals; roztoky; Gelatin; Ferrous Compounds; rychlé neutrony; Boron Neutron Capture Therapy; Radiometry; fantomy radiodiagnostické; lidé; Monte Carlo Method; Radiotherapy Planning, Computer-Assisted; termoluminiscenční dozimetrie; prasata; Fast Neutrons; radiometrie; Nuclear Reactors; Solutions; voda; Humans; Water; plánování radioterapie pomocí počítače; metoda Monte Carlo; Swine; Czech Republic; Phantoms, Imaging; želatina; Česká republika; atomové reaktory; železnaté sloučeniny; zvířata; Thermoluminescent Dosimetry; terapie metodou neutronového záchytu (bor-10)